1989
DOI: 10.1080/02827588909382569
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic changes in progenies of northern clones of Picea abies (L) Karst. grown in a southern seed orchard

Abstract: Of Forest Research NLH, Norway). Phenotypic changes in progenies of northern clones of Picea abies (L.) Karst, grown in a southern seed orchard. I. Frost hardiness in a phytotron experiment. Accepted Sept. 12, 1988. Scand. J. For. Res. 4: 317-330, 1989 Results are presented from artificial freezing tests comparing young controlled crossed progenies from the southern seed orchard at Lyngdal (58° N) with open-pollinated progenies from the same mother trees standing in the northern natural forest (63°-66°N). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 34 publications
1
51
1
1
Order By: Relevance
“…Seed weight, depends on reserve food material, which is produced as a result of double fertilization (endosperm) and is dominated by the maternal traits and is also influenced by the nutrient availability at the time of seed setting and environmental factors (Allen, 1960;Johnsen et al, 1989). Embryo development and its physiological function are contributed by the maternal as well as by paternal (pollen grain) traits in the species.…”
Section: Discussionmentioning
confidence: 99%
“…Seed weight, depends on reserve food material, which is produced as a result of double fertilization (endosperm) and is dominated by the maternal traits and is also influenced by the nutrient availability at the time of seed setting and environmental factors (Allen, 1960;Johnsen et al, 1989). Embryo development and its physiological function are contributed by the maternal as well as by paternal (pollen grain) traits in the species.…”
Section: Discussionmentioning
confidence: 99%
“…and Scotch pine (Pinus sylvestris L.) should be mentioned. In repeated experiments, seeds produced from controlled crosses in a warm climate gave seedlings with an extended growth period and delayed frost hardening as compared with seedlings from similar crosses made in a cooler climate (Bjprnstad 1981, Johnsen 1989.The mechanisms for these effects are not known, but some evidence suggests a climatic effect (genetic or epigenetic) during pollination and fertilization (Johnsen et al, unpublished). Andersen (1971) has shown that the wintering capacity of a timothy cultivar can be significantly reduced after a few generations of seed production in a southern location.…”
Section: Genetic Aspects Of Adaptationmentioning
confidence: 99%
“…Positive (+) and negative (-) pointer years of spherical-and conical spruces for the northern part of the study region for the time period 1920. Year 19221926193319351958196819731975197619891997 Spherical trees…”
Section: Discussionmentioning
confidence: 99%
“…Sylvén 1909, Gruber 1988, growth rhythm and frost hardiness (e.g. Johnsen 1989, Skroppa 1994, or needle morphology and photosynthesis (e.g. Ishii et al 2007 in Picea jezoensis).…”
Section: Introductionmentioning
confidence: 99%